2006
DOI: 10.1210/jc.2005-1986
|View full text |Cite
|
Sign up to set email alerts
|

123I Thyroid Uptake and Thyroid Size at 24, 48, and 72 Hours after the Administration of Recombinant Human Thyroid-Stimulating Hormone to Normal Volunteers

Abstract: Context: Recombinant human TSH (rhTSH) is used to evaluate thyroid carcinoma patients and off-label for 131 I thyroid ablation and nontoxic goiter therapy.Objective: Our objective was to determine the optimal time for 131 I administration after rhTSH.Participants: Twenty-five euthyroid nongoitrous volunteers participated in the study.Design: Baseline 24-h thyroid 123 I uptake (RAIU) was measured, and then 0.1 mg rhTSH was administered.123 I was administered 24, 48, or 72 h after rhTSH, and a repeat 24-h RAIU … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 22 publications
2
24
1
Order By: Relevance
“…Our results indicate that the response to rhTSH in goiter patients, compared with healthy individuals, may differ. Although we observed a similar trend (the effect of rhTSH decreased with intervals longer than 24 h), we found that the RAIU was still significantly increased (by 62%) in the rhTSH/72-h group, in contrast to no response seen in healthy individuals (7). Apparently the morphologic or physiologic changes in goiter tissue cause a prolonged effect of rhTSH on RAIU.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Our results indicate that the response to rhTSH in goiter patients, compared with healthy individuals, may differ. Although we observed a similar trend (the effect of rhTSH decreased with intervals longer than 24 h), we found that the RAIU was still significantly increased (by 62%) in the rhTSH/72-h group, in contrast to no response seen in healthy individuals (7). Apparently the morphologic or physiologic changes in goiter tissue cause a prolonged effect of rhTSH on RAIU.…”
Section: Discussionsupporting
confidence: 71%
“…In an uncontrolled trial including 25 healthy individuals (7)-also using 0.1 mg of rhTSH-the same intervals (24,48, and 72 h) between rhTSH and 131 I tracer administration were investigated. In that study (7), the relative increase in 24-h RAIU was 88%, 36%, and 0%, respectively, in the 24-, 48-, and 72-h rhTSH groups. Our results indicate that the response to rhTSH in goiter patients, compared with healthy individuals, may differ.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Defining a lower dose limit that increases RAIU sufficiently is paramount, since adverse effects, especially the induction of transient thyrotoxicosis, are dose dependent (40)(41)(42). The changes in thyroid RAIU following rhTSH doses between 0.01 and 0.9 mg have been investigated in both healthy individuals and patients with MNG (Table 1).…”
Section: Radioiodine Therapy With Rhtsh Pre-stimulationmentioning
confidence: 99%
“…In addition, measurements of RAIU are extremely prone to variation in the method used. Despite these shortcomings, studies in MNG patients (19,20,40,(43)(44)(45)(46) and healthy individuals (41,42,47) document an approximately twofold increase in RAIU, largely independent of rhTSH dose. In support of this observation, a small comparative trial found that 0.03 mg was not superior to 0.01 mg (40) and another comparative trial observed that 0.3 mg was not superior to 0.1 mg (45).…”
Section: Radioiodine Therapy With Rhtsh Pre-stimulationmentioning
confidence: 99%